Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/chem.202203366
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Mediated Radio‐Iodination of Arenes by Using Organosilane and Organogermane as Radiolabelling Precursors

Abstract: The radio-iodination of arenes is investigated from organosilane and organogermane precursors using ipsoelectrophilic halogenation (IEH). Discovery of a mild base mediated process allows radio-iodination in HFIP (1,1,1,3,3,3hexafluoro-2-propanol) of either aryl silane or germane, with germanes being more reactive. Clinical potential of arylger-manes as radio-iodination precursors is demonstrated through the labelling of [ 125 I]IMTO (iodometomidate) and [ 125 I]MIBG (meta-iodobenzylguanidine) thus offering an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…However, we still suggest that "the silanol activation pathway" is dominant for the O-germylation considering the expected higher acidity of silanols compared to alkynylgermanes. In the case of sp C-germylation, 1 H NMR analysis confirmed a deprotonation step (no signal for the acetylenic proton, for details please see SI). Subsequently, it is suggested that formed acetylide reacts with bis(triorganogermyl) www.nature.com/scientificreports/ acetylene to generate pentacoordinated germanium intermediates.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, we still suggest that "the silanol activation pathway" is dominant for the O-germylation considering the expected higher acidity of silanols compared to alkynylgermanes. In the case of sp C-germylation, 1 H NMR analysis confirmed a deprotonation step (no signal for the acetylenic proton, for details please see SI). Subsequently, it is suggested that formed acetylide reacts with bis(triorganogermyl) www.nature.com/scientificreports/ acetylene to generate pentacoordinated germanium intermediates.…”
Section: Resultsmentioning
confidence: 98%
“…This strategy has provided an entry point into various organogermanes including germasiloxanes and alkynylgermanes. Remarkably, not only KHMDS but also simple bases such as KOH can serve as efficient catalysts in this process.Organogermanium compounds are much less studied than their silicon counterparts, but very recently, an impetus to design new synthetic routes to various organogermanes was witnessed and significant contributions were reported [1][2][3][4][5][6][7][8][9][10][11] . That is not merely a scientific curiosity but primarily, the unique features of germanium compounds are the leading cause of this trend.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Select examples of ipso-halogenation of trialkylgermanes by A) Matsunaga and co-workers [28] B) Schoenebeck and co-workers. [29,30] Angewandte Chemie untouched, whilst the alternative reactive sites were readily functionalised when subjected to established Pd 0 / Pd II -catalyzed CÀ O bond-forming, Ullman-type, Ni/photoredox, or ChanÀ Lam conditions. [31] As a result, fully orthogonal reactivity of organogermanes to alternative coupling partners was once again demonstrated.…”
Section: Cà O Bond Formationmentioning
confidence: 99%
“…Organogermanium compounds have found wide applications in synthesis, [1][2][3][4][5][6][7][8][9] drug discovery 10 and materials science. 11 This utility is attributable to the relatively high stability and low toxicity (Fig.…”
mentioning
confidence: 99%